Analisis Social Media Marketing dan Brand Love terhadap Loyalty Brand Studi Pemasaran Produk Skintific Pada Followers Kawaidollshop - Angellita Zulfa Ferrati Vutri; Kokom Komariah; Faizal Mulia Z (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to analyze social media maeketing and bran love on brand loyalty of Skintific products to Kawaidollshop Sukabumi instagram followers, to demine the effect of social media marketing on brand loyalty of Skintific product to Kawaidollshop Sukabumi instagram followers, and to demine the effect of brand love on product brand loyalty Skintific on Kawaidollshop Sukabumi followers. The types of research method used by researchers is a quantitative method with associative descriptive appoach. The population in this study amounted to 249 thousand who were instagram followers Kawaidollshop with a sample of 152 respondents. The sampling method uses cluster random sampling. The data analysis technique in this study used IBM SPSS 26 software. The data analysis used was the normality test, multiple linear regression analysis, coefficient of determination test, simultaneous significant test (f test) and partial significant test (t test). The findings in ths study are partially known that social media marketing variables (X1) and brand love variable (X2) each have a positive and significant effect on brand loyalty (Y). Simultaneously, social media marketing (X1) and brand love (X2) have a positive and significant effect on brand loyalty (Y). Keywords : Loyalty brand, social media marketing, brand love